2022
DOI: 10.3390/jcm11216569
|View full text |Cite
|
Sign up to set email alerts
|

No Significant Differences in Clinical and Radiographic Outcomes between PCL Retained or Sacrificed Kinematic Aligned Medial Pivot Total Knee Arthroplasty in Varus Knee

Abstract: In the last decades, several surgical techniques, such as medial pivot (MP) philosophy and kinematic alignment (KA), have been introduced in total knee arthroplasty (TKA) to improve patients’ outcomes. This retrospective study aims to evaluate the clinical, radiographic, and functional results of PCL preservation or sacrifice in KA MP-TKA. A consecutive series of 147 patients older than 60, with a minimum follow-up of two years, were treated with TKA for severe primary knee osteoarthritis (OA) at the Departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
1
9
1
Order By: Relevance
“…These PROM results were similar to the present study. Whilst the FJS in the present study was less than Nedopil's cohort, the mean was higher in our study when compared to the unrestricted calipered groups of both PCL preserved and sacrificed in Giustra et al's [9] study. Other studies using technology‐based platforms to achieve KA showed similar results, including McEwen et al [25], who conducted a randomised controlled trial on computer‐assisted KA.…”
Section: Discussioncontrasting
confidence: 78%
“…These PROM results were similar to the present study. Whilst the FJS in the present study was less than Nedopil's cohort, the mean was higher in our study when compared to the unrestricted calipered groups of both PCL preserved and sacrificed in Giustra et al's [9] study. Other studies using technology‐based platforms to achieve KA showed similar results, including McEwen et al [25], who conducted a randomised controlled trial on computer‐assisted KA.…”
Section: Discussioncontrasting
confidence: 78%
“…Osteoarthritis is the most common disease of joints in the adult population [1][2][3][4]. In particular, the knee is the most frequent location for osteoarthritis, as its prevalence in adults is around 6%, rising as high as 40% among the 70-to-74-year-olds [5][6][7]. Knee osteoarthritis thereby represents a burden for national health systems, as it can lead to serious disability caused by increasing pain and progressive articular stifness that may limit patients' autonomy and thereby have a negative impact on their quality of life [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of TKA is restoring the native harmony of the knee. Three interdependent elements, including morphology, soft-tissue balance, and alignment, should be considered at the same time to reach this goal [ 29 , 30 ]. As shown in Figure 4 , MA, which solely focuses on alignment and ignores the other two elements, has a high ratio of dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%